PELATIHAN PEMBUATAN ABON DARI DAGING SAPI UNTUK MENAMBAH PENDAPATAN IBU-IBU RUMAH TANGGA - Kusuma Adhianto; Diki Danar Tri Winanti; Muhammad Husaini; Dian Kurniawati (Jurnal Media Pengabdian Kepada Masyarakat, 2022)
Beef is a source of food that is much needed and consumed by humans, because it has a high protein content. Protein has a function as a building, regulatory, and replacement substance for body parts or tissue that has been damaged. In addition, protein can also be a source of energy and contains essential amino acids needed by the human body. Beef is widely marketed by sellers and is easily available. Beef can be used to become shredded so that it has added value. Housewives in Rantau Fajar Village Raman Utara District Lampung Timur Regency have a habit after completing household tasks, they do not have other jobs. Usually they visit each other with neighbors and chat which is of no use. The team for community service at the University of Lampung plans to conduct training in making beef shredded to train housewives who do not have jobs to have the skills to make beef shredded. The aim of the training in making beef floss for housewives in Rantau Fajar Village Raman Utara District Lampung Timur Regency is to provide knowledge and skills to housewives so that they have skills. With the acquired skills, it is hoped that they can increase their household income. The results of the community service that were carried out received a very enthusiastic appreciation from the community, as well as increased public knowledge about how to make shredded beef which has high nutritional value, as well as technology transfer in the form of a slicer that separates the oil content from beef shredded.